Odstraňování CO2 z bioplynu - Kovář, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Prozkoumání technologií Selexol, Rectisol, Fluor a Purisol při úpravě bioplynu na kvalitu zemního plynu je hlavní náplní práce. Vyčištěný bioplyn musí splňovat kvalitativní požadavky, které stanovuje legislativa ČR. Důležitým bodem je sestavení simulačních modelů technologií v programu ChemCad. Pomocí nich jsou pak metody analyzovány při stejných výstupních požadavcích. Výsledkem je určit, zda jsou technologie pro čištění bioplynu vhodné a provést, formou rešerše, zjednodušené technicko-ekonomické zhodnocení.

Research the Selexol, Rectisol, Fluor and Purisol technologies for the treatment of biogas to natural gas quality is the main job. The purified biogas must meet quality requirements, which sets out legislation Czech Republic. An important point is to build models of technology in the ChemCad software. Methods are analyzed with these models for the same output requirements. The result is to determine whether the technologies are suitable for biogas purification and implement, through research, simplified technical and economic evaluation.
CO2 removing from biogas
Keywords: Bioplyn; Biometan; Úprava bioplynu; Absorpce; Oxid uhličitý; Proces Selexol; Proces Rectisol; Proces Fluor; Proces Purisol; Simulační model; Biogas; Bio-methane; Upgrading biogas; Absorption; Carbon dioxide; Process Selexol; Process Rectisol; Process Fluor; Process Purisol; Simulation model